Technology Adoption Model of Electronic Public Administration Services in Croatia - Research Framework Proposition - Denis Hrestak (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
In the last few years we have witnessed the rapid development of electronic public administration services in the Republic of Croatia, while, at the same time, there are no clear indications what has an influence on the acceptance of such services. The purpose of this paper is the identification of factors that contribute to or hinder the adoption of electronic public administration services in the Republic of Croatia. The concept of electronic public administration services (eGovernment) is related to information technology that facilitates the process of information exchange, communication and transactions between state institutions, citizens and businesses. Although the eGovernment became available to everyone not everyone is using it. This research will try to give an answer to why is this so and what can be done to improve the acceptance of eGovernment.The research will help to detect factors that contribute to or hinder the adoption of eGovernment in Croatia and help to understand the impact of various characteristics such as demographics, security, and other, on the level of acceptance of eGovernment, the intended use of eGovernment services, and, finally, the actual use of these services. Some of the key questions here are whether the usefulness of available eGovernment services affects the intended use; whether the usability of ICT systems influences the intended use and whether perceived shortcomings affect the intended use of the eGoverment services. Primary research will be carried out by a structured questionnaire. The collected data will be statistically processed through quantitative econometric analysis that would confirm or deny the existence of a strong correlation between the above factors.
Keywords: O330; 330; ICT; technology; electronic public administration; Croatia; acceptance model; research; eGovernment